Water-based single-component acrylate special laminating glue and preparation method thereof
By introducing ionic liquid modified Beta nanomolecular sieve catalysts into the aqueous composite film glue, the problems of slow drying speed, poor water resistance and insufficient adhesiveness of the aqueous composite film glue are solved, and the bonding performance and curing speed are significantly improved. It is suitable for Various environments, performance is close to traditional solvent-based composite film glue.
Patent Information
- Application Number
- CN202411572828.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-14
AI Technical Summary
The slow drying speed of water-based composite glue, poor water resistance and insufficient adhesiveness, limits its use in production efficiency, low temperature environments and specific applications.
The beta nanomolecular sieve catalyst modified with ionic liquid is introduced to improve the curing speed, adhesive properties and water resistance of the glue by changing its pore structure and surface properties, and promote oxygen transfer to improve curing efficiency.
It significantly improves the adhesive performance, water resistance and curing speed of the glue, optimizes production efficiency and product quality, and is suitable for high humidity or low temperature environments, and its performance is close to or even surpasses traditional solvent-based composite film glue.
Smart Images

Figure CN119307208A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to a water-based single-component acrylic ester special laminating glue and a preparation method thereof. Background Art
[0002] Laminating adhesive refers to a kind of glue that laminates biaxially oriented polypropylene (BOPP) film on paper. It includes water-based laminating adhesive and oil-based laminating adhesive. At present, water-based laminating adhesive is the main product in China. With the continuous improvement of national environmental protection laws and regulations and the gradual increase of people's environmental awareness, it is a general trend for solvent-based products to become water-based. In the current situation of the domestic market, water-based laminating adhesive laminating is the mainstream of the market. Laminating adhesive is widely used in the field of printing technology, bonding of food soft packaging, bonding of dry kraft paper cement bags, synthetic leather and shoemaking industries, etc.
[0003] As an environmentally friendly adhesive, water-based laminating glue has been widely used in the printing and packaging industry in recent years. It has gradually replaced traditional solvent-based laminating glue with its non-toxic, non-flammable, pollution-free and safe characteristics. However, despite the many advantages of water-based laminating glue, it still faces some challenges and difficulties in its actual application.
[0004] First, the drying speed of water-based laminating glue is relatively slow, mainly because the volatilization speed of water is slower than that of organic solvents. This problem leads to reduced production efficiency and increased energy consumption. In order to solve this problem, some researchers and companies are exploring how to increase the solid content of glue or use cross-linking methods to speed up the drying speed, so as to improve production efficiency and reduce energy consumption.
[0005] Secondly, the water resistance of water-based laminating glue is relatively poor, which limits its use in some applications that require excellent water resistance. In addition, the antifreeze performance of water-based laminating glue in low temperature environments is not good, which to some extent limits its application in cold areas. In order to improve these properties, researchers are trying to improve the water resistance and antifreeze properties of glue by chemical modification or adding specific additives.
[0006] Finally, the adhesion of water-based laminating glue is also a concern. When bonding to certain materials such as ink surfaces, the adhesion of water-based laminating glue may not be as good as that of solvent-based glue. In order to improve the bonding performance, researchers are exploring the use of new polymer emulsions or adding tackifiers to enhance the bonding ability of glue.
[0007] In general, as an environmentally friendly adhesive, water-based laminating glue has some challenges in its application, but with the advancement of technology and the improvement of environmental awareness, its development prospects are still very broad. Through continuous technological innovation and improvement, water-based laminating glue is expected to play a greater role in the future packaging industry. Summary of the invention
[0008] The object of the present invention is to provide a water-based one-component acrylic ester special laminating glue and a preparation method thereof, wherein the preparation method introduces the Beta nano molecular sieve catalyst modified by an ionic liquid into the laminating glue. The ionic liquid has unique physical and chemical properties, such as high thermal stability, low volatility and good solvent properties. When these ionic liquids are used to modify the Beta nano molecular sieve, the activity and selectivity of its active center can be enhanced, and higher efficiency can be shown in the catalytic reaction, and the curing time of the glue can be reduced, and the adhesive properties and water resistance of the glue can be significantly improved. This is because the introduction of the ionic liquid not only enhances the active sites of the molecular sieve, but also improves its dispersibility and compatibility in the glue by changing its pore structure and surface properties. In addition, the high oxygen solubility and proton conductivity of the ionic liquid can promote the oxygen transmission of the glue during the curing process, thereby improving the curing efficiency and bonding strength. This improvement is particularly important for improving the application performance of the laminating glue under high humidity or low temperature conditions.
[0009] In order to solve the above technical problems, the present invention provides a water-based one-component acrylic ester special laminating glue and a preparation method thereof.
[0010] To achieve the above object, the present invention provides the following technical solution: a water-based one-component acrylic special laminating glue, characterized in that it comprises an emulsifier pretreatment liquid, a first emulsion and a second emulsion, The raw materials in the emulsifier pretreatment liquid are calculated by mass ratio, wherein the ionic liquid modified Beta nano molecular sieve catalyst: deionized water: emulsifier = 1:20-35:0.5-0.85; The raw materials in the first emulsion are calculated by mass ratio, wherein fatty alcohol polyoxyethylene ether: deionized water: methyl methacrylate: polysiloxane: hydroxy acrylate: chain initiator: amino-modified polysiloxane = 1:25-50:12-23:10-18:8-10:0.74-0.93:7-10; The raw materials in the second emulsion are calculated by mass ratio, 20% to 45% of the emulsifier pretreatment liquid: the first emulsion = 1:2 to 5; The raw materials are calculated by mass ratio of remaining emulsifier pretreatment liquid: colorant: hindered amine light stabilizer: low viscosity methyl silicone oil = 1:0~0.02:0~0.03:0.1~1.5, and the second emulsion is added thereto to prepare a water-based single-component acrylic special laminating adhesive.
[0011] Furthermore, the preparation method of the ionic liquid modified Beta nano molecular sieve catalyst comprises the following steps: Step 1: Dissolve ammonium nitrate in water and mix it evenly with white carbon black, and dry it at 60-80°C for 5-12 hours. The mass ratio is white carbon black: ammonium nitrate: water = 1: 0.2-0.4: 5-20; Step 2: Mix aluminum oxide and tetraethylammonium hydroxide solution, stir magnetically for 30 minutes at a speed of 500 r / min, so that the aluminum oxide is completely dissolved, and the mass ratio of aluminum oxide to tetraethylammonium hydroxide solution is 1:20-50; Step 3: Add the dried white carbon black to the solution prepared in step 2, mix well, and dry at 70°C for 6 to 8 hours to obtain a mixture, wherein the mass ratio of aluminum oxide to white carbon black is 1:25 to 50; Step 4: Grind the dried mixture in the above step 3 and transfer it into an open glass vessel, then transfer it into a hydrothermal reactor lining, add deionized water outside the glass vessel in the hydrothermal reactor lining, the mass of the deionized water is 2 to 5 times the mass of the mixture, and prevent the water outside the glass vessel from entering the glass vessel, adjust the hydrothermal reactor to 165° C. under steam-assisted conditions, and crystallize the mixture, and crystallize for 8 to 20 hours to obtain a crystalline product; Step 5: After the crystal product is naturally cooled to room temperature, it is washed twice and dried, and calcined at 500-600 °C in air atmosphere for 12 h to obtain Beta nano molecular sieve; Step 6: Weigh chloroaluminate ionic liquid in a beaker, dissolve it in chloroform at 20-30°C until the solution is clear and transparent, add Beta nano molecular sieve, and stir at room temperature for 12 hours. The raw materials are calculated by mass ratio of Beta nano molecular sieve: chloroaluminate ionic liquid: chloroform = 1:1-5:15-35. After the end, filter, wash repeatedly with ether 3 times, and dry under vacuum conditions at 85-95°C for 12 hours. The ionic liquid modified Beta nano molecular sieve catalyst can be obtained.
[0012] Furthermore, the composition of the chain initiator is, by mass ratio, tert-dodecyl mercaptan: ammonium persulfate: deionized water = 0.2-0.4: 0.02-0.04: 1.
[0013] Furthermore, the emulsifier is one or more of sodium allyloxyhydroxypropyl sulfonate, sodium olefinoxy sulfonate and polyoxyethylene polyol carboxylate.
[0014] Furthermore, the colorant is a pigment such as black, red, blue, yellow, green, etc.
[0015] A method for preparing a water-based one-component acrylic special laminating glue, characterized in that it comprises the following steps: Step 1: Add the ionic liquid modified Beta nano molecular sieve catalyst into deionized water, and after ultrasonic dispersion for 15 to 30 minutes, add the emulsifier thereto, stir for 10 to 20 minutes, and continue ultrasonication for 15 minutes to obtain an emulsifier pretreatment solution; Step 2: Add fatty alcohol polyoxyethylene ether to deionized water, stir for 10 to 15 minutes, add methyl methacrylate thereto, stir for 20 minutes, add polysiloxane, continue to stir for 20 minutes, add hydroxy acrylate, stir for 20 minutes, add chain initiator, slowly add amino-modified polysiloxane while stirring, heat to 65 to 75° C. after adding, keep warm for 1 to 1.5 hours, keep stirring during the whole process, to obtain a first emulsion; Step 3: Add 20% to 45% of the emulsifier pretreatment liquid to the first emulsion, stir and heat to 95 to 100°C, and keep warm for 40 to 60 minutes to obtain a second emulsion, wherein the mass ratio of the added 20% to 45% emulsifier pretreatment liquid to the first emulsion is 1:2 to 5; Step 4: Add colorant, hindered amine light stabilizer and low viscosity methyl silicone oil to the remaining emulsifier pretreatment liquid, stir for 45 to 65 minutes, then add the second emulsion, stir for 30 minutes, heat to 50 to 60 ° C and keep warm for 1 hour, then cool and filter with a 300 mesh filter to obtain a water-based one-component acrylic special laminating adhesive.
[0016] Furthermore, the stirring speed of the stirring is 400-800 r / min.
[0017] The present invention provides a water-based single-component acrylic special laminating glue and a preparation method thereof, which significantly improves multiple key performance indicators by introducing an ionic liquid-modified Beta nano-molecular sieve catalyst into the water-soluble laminating glue. This new type of laminating glue significantly improves the overall performance of the glue by reducing viscosity, enhancing adhesion and water resistance, and improving dispersibility and compatibility. The high thermal stability and excellent solvent properties of the Beta nano-molecular sieve catalyst effectively reduce the viscosity of the glue, optimize its fluidity and coating uniformity during high-speed laminating, thereby improving production efficiency and product quality.
[0018] Ionic liquids enhance the active centers of the Beta nano-molecular sieve catalyst, significantly enhancing the adhesive properties of the glue to a variety of substrates, whether plastic, metal or paper, to achieve strong bonding. The high specific surface area and porosity of the Beta nano-molecular sieve further enhance the dispersibility and compatibility of the glue, allowing it to better penetrate and adhere to porous or rough surfaces, thereby improving the firmness and overall performance of the coating. In addition, this catalyst also accelerates the curing speed of the glue, shortens the production cycle, and improves production efficiency, which is particularly important for large-scale production and fast packaging lines because it can directly translate into cost savings and higher output rates. In addition to the above-mentioned performance improvements, this laminating glue also exhibits other beneficial effects, such as improving the weather resistance and chemical resistance of the product, which is crucial for the application of packaging materials in changing environments. These improvements make the water-based one-component acrylic special laminating glue not only close to, but even surpass the traditional solvent-based laminating glue in some aspects, while maintaining the advantages of environmental protection and sustainability. With the continuous advancement of technology and the increasing maturity of the market, this new type of laminating glue is expected to play a greater role in the field of packaging materials in the future, providing strong support for achieving more environmentally friendly and efficient packaging solutions. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A flow chart of a water-based one-component acrylic special laminating glue and a preparation method thereof provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0021] See also Figure 1 , an embodiment of the present invention provides a water-based one-component acrylic ester special laminating glue and a preparation method thereof.
[0022] The functionalized acrylic modified polysiloxane heavy-duty anticorrosive coating and its preparation method provided by the present invention are specifically described below through examples. Example 1
[0023] Step 1: Add the ionic liquid modified Beta nano molecular sieve catalyst into deionized water, and after ultrasonic dispersion for 30 minutes, add sodium olefinoxysulfonate thereto, stir at 800 r / min for 20 minutes, and continue ultrasonication for 15 minutes to prepare an emulsifier pretreatment liquid, wherein the above raw materials are calculated by mass ratio of ionic liquid modified Beta nano molecular sieve catalyst: deionized water: sodium olefinoxysulfonate = 1:25:0.5; Step 2: Add fatty alcohol polyoxyethylene ether to deionized water, stir at 800 r / min for 15 minutes, add methyl methacrylate thereto, stir for 20 minutes, add polysiloxane, continue stirring for 20 minutes, add hydroxy acrylate, stir for 20 minutes, add chain initiator (tert-dodecyl mercaptan: ammonium persulfate: deionized water = 0.2:0.02:1), slowly add amino-modified polysiloxane while stirring, heat to 75°C after the addition is complete, keep warm for 1.5 hours, and keep stirring at 800 r / min throughout the process to obtain a first emulsion, wherein the above raw materials are calculated by mass ratio: fatty alcohol polyoxyethylene ether: deionized water: methyl methacrylate: polysiloxane: hydroxy acrylate: chain initiator: amino-modified polysiloxane = 1:35:18:16:8:0.76:8; Step 3: Add 45% of the emulsifier pretreatment liquid to the first emulsion, stir at 800r / min and heat to 100°C, keep warm for 40 minutes to prepare a second emulsion, wherein the mass ratio of the added 20% to 45% of the emulsifier pretreatment liquid to the first emulsion is 1:3.5; Step 4: Add hindered amine light stabilizer and low viscosity methyl silicone oil to the remaining 55% emulsifier pretreatment liquid, wherein the raw materials are calculated by mass ratio, emulsifier pretreatment liquid: hindered amine light stabilizer: viscosity methyl silicone oil = 1:0.03:0.35, stir at 800r / min for 60 minutes, add the above second emulsion, stir for 30 minutes, heat to 60°C and keep warm for 1 hour, then cool down and filter with a 300-mesh filter to obtain a water-based one-component acrylate special laminating adhesive.
[0024] The preparation method of the ionic liquid modified Beta nano molecular sieve catalyst comprises the following steps: Step 1: Dissolve ammonium nitrate in water and mix it evenly with white carbon black, and dry it at 60°C for 8 hours. The mass ratio is white carbon black: ammonium nitrate: water = 1:0.2:5~20; Step 2: Mix aluminum oxide and tetraethylammonium hydroxide solution, and stir magnetically for 30 minutes at a speed of 500 r / min to completely dissolve the aluminum oxide. The mass ratio of aluminum oxide to tetraethylammonium hydroxide solution is 1:25. Step 3: Add the dried white carbon black to the solution prepared in step 2, mix well, and dry at 70°C for 6 hours to obtain a mixture, the mass ratio of which is aluminum oxide: white carbon black = 1:50; Step 4: Grind the dried mixture in the above step 3 and transfer it into an open glass vessel, then transfer it into a hydrothermal reactor lining, add deionized water outside the glass vessel in the hydrothermal reactor lining, the mass of the deionized water is 3 times the mass of the mixture, and prevent the water outside the glass vessel from entering the glass vessel, adjust the hydrothermal reactor to 165° C. under steam-assisted conditions, and crystallize the mixture, and crystallize for 10 hours to obtain a crystalline product; Step 5: After the crystal product is naturally cooled to room temperature, it is washed twice and dried, and calcined at 550 °C in air atmosphere for 12 h to obtain Beta nano molecular sieve; Step 6: Weigh chloroaluminate ionic liquid in a beaker, dissolve it in chloroform at 20-30°C until the solution is clear and transparent, add Beta nano molecular sieve, and stir at room temperature for 12 hours. The raw materials are calculated by mass ratio of Beta nano molecular sieve: chloroaluminate ionic liquid: chloroform = 1:3:20. After the end, filter, wash repeatedly with ether 3 times, and dry at 90°C under vacuum for 12 hours. The ionic liquid modified Beta nano molecular sieve catalyst can be obtained. Example 2
[0025] Step 1: Add the ionic liquid modified Beta nano molecular sieve catalyst into deionized water, and after ultrasonic dispersion for 30 minutes, add sodium allyloxy hydroxypropyl sulfonate thereto, stir at 800 r / min for 20 minutes, and continue ultrasonication for 15 minutes to prepare an emulsifier pretreatment liquid, wherein the above raw materials are calculated by mass ratio of ionic liquid modified Beta nano molecular sieve catalyst: deionized water: sodium olefinoxy sulfonate = 1:35:0.6; Step 2: Add fatty alcohol polyoxyethylene ether to deionized water, stir at 800 r / min for 15 minutes, add methyl methacrylate thereto, stir for 20 minutes, add polysiloxane, continue stirring for 20 minutes, add hydroxy acrylate, stir for 20 minutes, add chain initiator (tert-dodecyl mercaptan: ammonium persulfate: deionized water = 0.2:0.02:1), slowly add amino-modified polysiloxane while stirring, after adding, heat to 75°C, keep warm for 1.5 hours, keep stirring at 800 r / min throughout the process, and prepare the first emulsion, wherein the above raw materials are calculated by mass ratio: fatty alcohol polyoxyethylene ether: deionized water: methyl methacrylate: polysiloxane: hydroxy acrylate: chain initiator: amino-modified polysiloxane = 1:45:20:18:9:0.75:10; Step 3: Add 45% of the emulsifier pretreatment liquid to the first emulsion, stir at 800r / min and heat to 100°C, keep warm for 40 minutes to prepare a second emulsion, wherein the mass ratio of the added 20% to 45% of the emulsifier pretreatment liquid to the first emulsion is 1:3; Step 4: Add red colorant, hindered amine light stabilizer and low viscosity methyl silicone oil to the remaining 55% emulsifier pretreatment liquid, wherein the raw materials are calculated by mass ratio as follows: emulsifier pretreatment liquid: red colorant: hindered amine light stabilizer: viscosity methyl silicone oil = 1:0.003:0.02:0.35. After stirring at 800r / min for 60 minutes, add the above second emulsion, stir for 30 minutes, heat to 60°C and keep warm for 1 hour, then cool down and filter with a 300-mesh filter to obtain a water-based one-component acrylate special laminating adhesive.
[0026] The preparation method of the ionic liquid modified Beta nano molecular sieve catalyst is shown in Example 1. Example 3
[0027] Step 1: Add the ionic liquid modified Beta nano molecular sieve catalyst into deionized water, and after ultrasonic dispersion for 30 minutes, add sodium allyloxy hydroxypropyl sulfonate thereto, stir at 800 r / min for 20 minutes, and continue ultrasonication for 15 minutes to prepare an emulsifier pretreatment liquid, wherein the above raw materials are calculated by mass ratio of ionic liquid modified Beta nano molecular sieve catalyst: deionized water: sodium olefinoxy sulfonate = 1:28:0.8; Step 2: Add fatty alcohol polyoxyethylene ether to deionized water, stir at 800 r / min for 15 minutes, add methyl methacrylate thereto, stir for 20 minutes, add polysiloxane, continue stirring for 20 minutes, add hydroxy acrylate, stir for 20 minutes, add chain initiator (tert-dodecyl mercaptan: ammonium persulfate: deionized water = 0.2:0.02:1), slowly add amino-modified polysiloxane while stirring, after adding, heat to 75°C, keep warm for 1.5 hours, keep stirring at 800 r / min throughout the process, and prepare the first emulsion, wherein the above raw materials are calculated by mass ratio: fatty alcohol polyoxyethylene ether: deionized water: methyl methacrylate: polysiloxane: hydroxy acrylate: chain initiator: amino-modified polysiloxane = 1:25:12:13:9:0.74:10; Step 3: Add 35% of the emulsifier pretreatment liquid to the first emulsion, stir at 800r / min and heat to 100°C, keep warm for 40 minutes to prepare a second emulsion, wherein the mass ratio of the added 20% to 45% of the emulsifier pretreatment liquid to the first emulsion is 1:2; Step 4: Add hindered amine light stabilizer and low viscosity methyl silicone oil to the remaining 65% emulsifier pretreatment liquid, wherein the raw materials are calculated by mass ratio, emulsifier pretreatment liquid: hindered amine light stabilizer: viscosity methyl silicone oil = 1:0.03:0.25, stir at 800r / min for 60 minutes, add the above second emulsion, stir for 30 minutes, heat to 60°C and keep warm for 1 hour, then cool down, filter with a 300-mesh filter to obtain a water-based one-component acrylate special laminating adhesive.
[0028] The preparation method of the ionic liquid modified Beta nano molecular sieve catalyst is shown in Example 1.
[0029] The water-based one-component acrylic special laminating glue obtained in Example 1 was tested to obtain the data shown in Table 1. Table 1 project Example 1 Detection Methods Appearance Transparent fluid without impurities Visual inspection Solid content ≥40 GB-2796 Viscosity (25℃, mPa.s) 265 GB / T1723-1976 PP-paper peeling strength (N / 25mm) ≥5.5 GB / T8809-1988 PP film-PP film peel strength (N / 25mm) ≥7.5 GB / T8809-1988 Wire pressing test No separation, no whitish Press the line 30 minutes after lamination, and then bake at 50℃ for 120 minutes Ink peeling test The ink print on the color printing paper is evenly transferred to the PP film Manual film peeling standard CY / T7.7-91 Baking test No bubbles, no delamination, no wrinkles 60-65℃, drying for 30 minutes, standard CY / T7.7-91 Blister test No separation, no bubbles Soak in cold water for 120 minutes, standard CY / T7.7-91 Enhanced aging test No separation, peel strength decrease ≤18% 250 hours under strong light at 40℃ Natural aging test Peel strength decrease ≤ 20% Exposure indoors for five months at room temperature Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A water-based one-component acrylic special laminating glue, characterized in that: It includes an emulsifier pretreatment liquid, a first emulsion and a second emulsion, The raw materials in the emulsifier pretreatment liquid are calculated by mass ratio, wherein the ionic liquid modified Beta nano molecular sieve catalyst: deionized water: emulsifier = 1:20-35:0.5-0.85; The raw materials in the first emulsion are calculated by mass ratio, wherein fatty alcohol polyoxyethylene ether: deionized water: methyl methacrylate: polysiloxane: hydroxy acrylate: chain initiator: amino-modified polysiloxane = 1:25-50:12-23:10-18:8-10:0.74-0.93:7-10; The raw materials in the second emulsion are calculated by mass ratio, 20% to 45% of the emulsifier pretreatment liquid: the first emulsion = 1:2 to 5; The raw materials are calculated by mass ratio of remaining emulsifier pretreatment liquid: colorant: hindered amine light stabilizer: low viscosity methyl silicone oil = 1:0~0.02:0~0.03:0.1~1.5, and the second emulsion is added thereto to prepare a water-based single-component acrylic special laminating adhesive.
2. The water-based one-component acrylic special laminating glue according to claim 1, characterized in that: The preparation method of the ionic liquid modified Beta nano molecular sieve catalyst comprises the following steps: Step 1: Dissolve ammonium nitrate in water and mix it evenly with white carbon black, and dry it at 60-80°C for 5-12 hours. The mass ratio is white carbon black: ammonium nitrate: water = 1: 0.2-0.4: 5-20; Step 2: Mix aluminum oxide and tetraethylammonium hydroxide solution, stir magnetically for 30 minutes at a speed of 500 r / min, so that the aluminum oxide is completely dissolved, and the mass ratio of aluminum oxide to tetraethylammonium hydroxide solution is 1:20-50; Step 3: Add the dried white carbon black to the solution prepared in step 2, mix well, and dry at 70°C for 6 to 8 hours to obtain a mixture, wherein the mass ratio of aluminum oxide to white carbon black is 1:25 to 50; Step 4: Grind the dried mixture in the above step 3 and transfer it into an open glass vessel, then transfer it into a hydrothermal reactor lining, add deionized water outside the glass vessel in the hydrothermal reactor lining, the mass of the deionized water is 2 to 5 times the mass of the mixture, and prevent the water outside the glass vessel from entering the glass vessel, adjust the hydrothermal reactor to 165° C. under steam-assisted conditions, and crystallize the mixture, and crystallize for 8 to 20 hours to obtain a crystalline product; Step 5: After the crystal product is naturally cooled to room temperature, it is washed twice and dried, and calcined at 500-600 °C in air atmosphere for 12 h to obtain Beta nano molecular sieve; Step 6: Weigh chloroaluminate ionic liquid in a beaker, dissolve it in chloroform at 20-30°C until the solution is clear and transparent, add Beta nano molecular sieve, and stir at room temperature for 12 hours. The raw materials are calculated by mass ratio of Beta nano molecular sieve: chloroaluminate ionic liquid: chloroform = 1:1-5:15-35. After the end, filter, wash repeatedly with ether 3 times, and dry under vacuum conditions at 85-95°C for 12 hours. The ionic liquid modified Beta nano molecular sieve catalyst can be obtained.
3. The water-based one-component acrylic special laminating glue according to claim 1, characterized in that: The composition of the chain initiator is, by mass ratio, tert-dodecyl mercaptan: ammonium persulfate: deionized water = 0.2-0.4: 0.02-0.04:
1.
4. The water-based one-component acrylic special laminating glue according to claim 1, characterized in that: The emulsifier is one or more of sodium allyloxyhydroxypropyl sulfonate, sodium olefinoxy sulfonate and polyoxyethylene polyol carboxylate.
5. The water-based one-component acrylic special laminating glue according to claim 1, characterized in that: The colorant is a pigment such as black, red, blue, yellow, green, etc.
6. The method for preparing a water-based one-component acrylic special laminating glue according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Add the ionic liquid modified Beta nano molecular sieve catalyst into deionized water, and after ultrasonic dispersion for 15 to 30 minutes, add the emulsifier thereto, stir for 10 to 20 minutes, and continue ultrasonication for 15 minutes to obtain an emulsifier pretreatment solution; Step 2: Add fatty alcohol polyoxyethylene ether to deionized water, stir for 10 to 15 minutes, add methyl methacrylate thereto, stir for 20 minutes, add polysiloxane, continue to stir for 20 minutes, add hydroxy acrylate, stir for 20 minutes, add chain initiator, slowly add amino-modified polysiloxane while stirring, heat to 65 to 75° C. after adding, keep warm for 1 to 1.5 hours, keep stirring during the whole process, to obtain a first emulsion; Step 3: Add 20% to 45% of the emulsifier pretreatment liquid to the first emulsion, stir and heat to 95 to 100°C, and keep warm for 40 to 60 minutes to obtain a second emulsion, wherein the mass ratio of the added 20% to 45% emulsifier pretreatment liquid to the first emulsion is 1:2 to 5; Step 4: Add colorant, hindered amine light stabilizer and low viscosity methyl silicone oil to the remaining emulsifier pretreatment liquid, stir for 45 to 65 minutes, then add the second emulsion, stir for 30 minutes, heat to 50 to 60 ° C and keep warm for 1 hour, then cool and filter with a 300 mesh filter to obtain a water-based one-component acrylic special laminating adhesive.
7. The method for preparing a water-based one-component acrylic special laminating glue according to claim 6, characterized in that: The stirring speed of the stirring is 400-800 r / min.